"LANDSCAPISM" AT THE SPEED OF LIGHT: DARKNESS AND ILLUMINATION IN MOTION. Issue 1 (March 2015) - Edensor, Tim; Lorimer, Hayden
ABSTRACT In conditions of darkness, how is landscape experienced when mediated by the artful staging of mass movement and artificial illumination? The article offers a response to this question of perception, phenomena and sensation, through culturally informed consideration of Speed of Light, a performance event staged in Holyrood Park, produced by arts charity NVA, during the 2012 Edinburgh International Festival. Speed of Light was a large‐scale, open‐air public artwork, illuminating the form and motion of walkers and runners, fusing the role of performer and spectator. Following an introduction to the event's design and delivery, and consideration of recent literatures on spaces of darkness and the illumination of landscape in contemporary social life, the authors describe and explain their respective roles as participating walker and runner in Speed of Light, and offer a series of participant‐informed interpretations. Observations arising from the social experience of darkness, illumination and motion, lead to closing reflections on what is termed "landscapism". Landscapism, a sensibility encapsulated in Speed of Light, is suggested as a transporting and enchanting affect achieved by estranging the expected encounter with topography and atmosphere. It is a staged sensibility that dramatizes the experience of looking at, listening to and feeling for the temporary transformation of landscape.